2016
DOI: 10.1111/febs.13912
|View full text |Cite
|
Sign up to set email alerts
|

Dehomocysteinylation is catalysed by the sirtuin‐2‐like bacterial lysine deacetylase CobB

Abstract: Hyperhomocysteinemia, which is characterized by elevated blood levels of the non-protein amino acid homocysteine (Hcy), is an independent risk factor for many diseases, including cardiovascular diseases, neurodegenerative diseases and birth defects. The incorporation of homocysteine into proteins, known as protein N-homocysteinylation, has been considered a major mechanism that contributes to hyperhomocysteinemia. However, the process of dehomocysteinylation, the N-homocysteinylation substrates and the regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…In addition to proteolytic turnover, N-Hcy residues can be removed from N-Hcy-protein by a dehomocysteinylation reaction, analogous to the deacetylation of protein Lys res-idues. A recent study shows that Cob-2, a Sir2-like bacterial Lys deacetylase, catalyzes dehomocysteinylation of N-Hcyprotein both in vitro and in vivo in the bacterium Salmonella enterica (212). Measurements of catalytic efficiencies with N-Hcy-Lys-peptide, N-acetyl-Lys-peptide, and Nsuccinyl-Lys-peptide as substrates indicate that the Cob-2 enzyme does not discriminate between these substrates and acts as a general N-acyl-Lys-peptide deacylase.…”
Section: Dehomocysteinylationmentioning
confidence: 99%
“…In addition to proteolytic turnover, N-Hcy residues can be removed from N-Hcy-protein by a dehomocysteinylation reaction, analogous to the deacetylation of protein Lys res-idues. A recent study shows that Cob-2, a Sir2-like bacterial Lys deacetylase, catalyzes dehomocysteinylation of N-Hcyprotein both in vitro and in vivo in the bacterium Salmonella enterica (212). Measurements of catalytic efficiencies with N-Hcy-Lys-peptide, N-acetyl-Lys-peptide, and Nsuccinyl-Lys-peptide as substrates indicate that the Cob-2 enzyme does not discriminate between these substrates and acts as a general N-acyl-Lys-peptide deacylase.…”
Section: Dehomocysteinylationmentioning
confidence: 99%
“…Perhaps the selectivity of CobB for certain substrates allows for greater promiscuity for removing various modifications. Indeed, CobB may be a deacylase capable of removing, in addition to acetyl groups, succinyl (143), propionyl (144, 145), lipoyl (146), and homocysteine (147) functional groups.…”
Section: Introductionmentioning
confidence: 99%
“…For E. coli, CobB was shown to affect the ac(et)ylation state of thousands of proteins and deletion of cobB resulted in upregulation of 10% of all acetylation sites in E. coli under the conditions of the study (Weinert et al, 2013a). Moreover, CobB removes diverse acyl-groups from lysine side chains suggesting to play a similar role as detoxifying enzyme suppressing low stoichiometry ac(et)ylation that might occur due to non-enzymatic ac(et)ylation by accumulation of ac(et)yl-CoA and acetyl-phosphate (Peng et al, 2011;AbouElfetouh et al, 2015;Mei et al, 2016;Weinert et al, 2017;Dong et al, 2019;Wei et al, 2019). Furthermore, it was shown that CobB does neither show preference nor discriminate between enzymatic and non-enzymatic acetylation sites (AbouElfetouh et al, 2015).…”
Section: Acetylphosphate-the Major Driver For Non-enzymatic Ac(et)ylation In Bacteriamentioning
confidence: 87%
“…Recently, CobB was shown be an efficient lipoamidase in analogy to mammalian SIRT4 acting on important lipoylated metabolic complexes, such as the α-ketoglutarate dehydrogenase (KDH) complex, the pyruvate dehydrogenase (PDH) complex and the glycine cleavage (GCV) complex and as de-2hydroxyisobutyrylase modulating enolase activity (Rowland et al, 2017;Dong et al, 2019). Furthermore, CobB was shown to act as de-homocysteinylase and it is supposed to revert protein lysine propionylation (Mei et al, 2016;Sun et al, 2016). SirTMs do not possess any deacylase activity, which is most likely due to the absence of the catalytic histidine residue (Rack et al, 2015;Olesen et al, 2018).…”
Section: Substrate Preference Of Bacterial Sirtuinsmentioning
confidence: 99%